2022
DOI: 10.3390/e24060776
|View full text |Cite
|
Sign up to set email alerts
|

Fermatean Fuzzy Schweizer–Sklar Operators and BWM-Entropy-Based Combined Compromise Solution Approach: An Application to Green Supplier Selection

Abstract: The Fermatean fuzzy set (FFS) is a momentous generalization of a intuitionistic fuzzy set and a Pythagorean fuzzy set that can more accurately portray the complex vague information of elements and has stronger expert flexibility during decision analysis. The Combined Compromise Solution (CoCoSo) approach is a powerful decision-making technique to choose the ideal objective by fusing three aggregation strategies. In this paper, an integrated, multi-criteria group-decision-making (MCGDM) approach based on CoCoSo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Combining three evaluation score strategies to make the final decision results more reasonable and superior, which not only avoids the problem of biased results caused by a single decision method but also effectively integrates multiple aggregation ideas to achieve internal balance and thus weakens the variability of decision results. Now the CoCoSo method is widely used in different areas, such as blockchain platform selection (Lai et al, 2022), logistics center site selection (Ulutas et al, 2020;Banihashemi et al, 2021), supplier selection (Yazdani et al, 2019b;Lai et al, 2020;Wang C. N. et al, 2022;Wei et al, 2022) due to its high flexibility and simple calculation.…”
Section: Evaluation Process Based On Entropy-cocoso Frameworkmentioning
confidence: 99%
“…Combining three evaluation score strategies to make the final decision results more reasonable and superior, which not only avoids the problem of biased results caused by a single decision method but also effectively integrates multiple aggregation ideas to achieve internal balance and thus weakens the variability of decision results. Now the CoCoSo method is widely used in different areas, such as blockchain platform selection (Lai et al, 2022), logistics center site selection (Ulutas et al, 2020;Banihashemi et al, 2021), supplier selection (Yazdani et al, 2019b;Lai et al, 2020;Wang C. N. et al, 2022;Wei et al, 2022) due to its high flexibility and simple calculation.…”
Section: Evaluation Process Based On Entropy-cocoso Frameworkmentioning
confidence: 99%
“…According to Table 5 , , , and appraise Z 1 , Z 2 , and Z 3 based on the above 26 criteria. According to relevant studies [ 63 , 100 , 101 , 102 , 103 , 104 ] and the context of the emergency material supplier selection problem, we use 10 language variables (ranging from Excellent to Very, Very Bad) and make decision makers choose the language variable that best fits the corresponding alternative for evaluation. All calculations in this paper are based on Matlab 2018a software.…”
Section: Illustrative Examplementioning
confidence: 99%
“…Wang et al ( 2023a ) propounded an improved version of CoCoSo method for T-SFS based on some novel Frank softmax aggregation operators, and the results showed that the improved method possesses some significant merits such as higher robustness and feasibility. Nevertheless, the CoCoSo approach is applied to different applications by scholars and researches (Deveci et al 2022 ; Lai et al 2022 ; Pamucar and Gorcun 2022 ; Panpatil et al 2022 ; Wei et al 2022 ; Zhang and Wei 2023 ; Zhu et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%